2023
DOI: 10.7759/cureus.46737
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Hypoxia Impact on Chronic Kidney Disease Onset and Progression: Review and Updates

Elmukhtar Habas,
Aisha Al Adab,
Mehdi Arryes
et al.

Abstract: Chronic kidney disease (CKD) is caused by hypoxia in the renal tissue, leading to inflammation and increased migration of pathogenic cells. Studies showed that leukocytes directly sense hypoxia and respond by initiating gene transcription, encoding the 2-integrin adhesion molecules. Moreover, other mechanisms participate in hypoxia, including anemia. CKD-associated anemia is common, which induces and worsens hypoxia, contributing to CKD progression. Anemia correction can slow CKD progression, but it should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 284 publications
0
2
0
Order By: Relevance
“…Similar to ndings from other studies that reported proteinuria is traditionally regarded as single most important risk factor for developing CKD and CKD progression (55,56). Anaemia is a signi cant risk factor for CKD and CKD progression; correction of anaemia improves quality of life and may slow down CKD progression (57,58) (70,71). Electrolyte imbalances and hyperkalemia are life threatening conditions that often occur in patients with CKD and CKD progression (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ndings from other studies that reported proteinuria is traditionally regarded as single most important risk factor for developing CKD and CKD progression (55,56). Anaemia is a signi cant risk factor for CKD and CKD progression; correction of anaemia improves quality of life and may slow down CKD progression (57,58) (70,71). Electrolyte imbalances and hyperkalemia are life threatening conditions that often occur in patients with CKD and CKD progression (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…During the progression of CKD, activation of the Renin-Angiotensin-Aldosterone System leads to tubular atrophy, alterations in tubular sodium ion concentration, and changes in filtrate flow rate. Angiotensin II (Ang II) induces afferent arteriolar contractions, reducing peritubular capillary perfusion and causing tubulointerstitial hypoxia [ 14 ]. Additionally, Ang II directly harms endothelial cells by inducing OS through NADPH oxidase activation, leading to peritubular capillary loss and subsequent cellular hypoxia due to inefficient respiration in tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%